Visualizing catalyst heterogeneity by a multifrequential oscillating reaction - Yuri Suchorski (Nature Portfolio, 2018)
The structurally different domains of a polycrystalline material may exhibit differing catalytic properties. Here, the authors directly visualize this phenomenon by observing the catalytic hydrogen oxidation that oscillates, simultaneously exhibiting different frequencies for structurally different rhodium domains.